Peran Guru Bimbingan dan Konseling Islam Dalam Menumbuhkan Sikap Disiplin Siswa MTS Al-Ghozaly Wonosobo - Muhamad Yusup; Sri Haryanto; Vava Imam Agus Faisal (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Being late for school, not going to class during class time, not dressing according to the applicable rules, and not wearing complete attributes are the behaviors of students that the author found at MTs Al-Ghozaly Wonosobo. The above actions are undisciplined behavior of students because discipline is an adjustment to a situation, where a person is able to move and regulate himself in all things with his own control, and must adapt to religious values ​​and norms that apply in the environment. public. Therefore, students are expected to learn discipline, and teachers always monitor the behavior of their students, to avoid disciplinary actions occurring because a teacher's job is not only to deliver learning material, but more than that, a teacher must build competence and students through the learning process and through guidance and counseling approaches. This research aims to determine the role of guidance and counseling teachers in fostering students' disciplinary attitudes. This research was carried out from April to May 2024 at MTs Al-Ghozali Wonosobo. The research uses field research with descriptive qualitative methods. Researchers use techniques and data collection, namely: 1). observation techniques, 2). interview, 3). documentation. From the data that researchers obtained, the researchers obtained results of quite good quality. Thus the researcher concluded that the role of guidance and counseling teachers in implementing guidance and counseling service activities in fostering students' disciplinary attitudes at MTs Al-Ghozaly Wonosobo, guidance and counseling teachers can be mentors, references and guidelines, controllers and controllers. Where guidance and counseling teachers always monitor the behavior of their students during school hours, so that there are no misbehavior or disciplinary actions. Guidance and counseling teachers should convey understanding to all students regarding the importance of discipline and counseling guidance services, and add guidance and counseling service activities, especially services that can foster student discipline at MTs Al-Ghozali Wonosobo.